Evaluation of food and nutrient intake in a population of subjects affected by periodontal disease with different levels of bone mineral density - Guasti, Leonardo; Cianferotti, Luisella; Pampaloni, Barbara; Tonelli, Francesco; Martelli, Francesco; Iantomasi, Teresa; Brandi, Maria Luisa (Frontiers in Endocrinology, 2023)
Introduction Both osteoporosis and periodontitis are pathologies characterized by an imbalance in the bone tissue. Vitamin C is an important factor involved in maintaining the health of the periodontium; its deficiency causes characteristic lesions to periodontal tissues such as bleeding and redness of the gums. Among the essential minerals for the health of the periodontium we find instead calcium. Objectives of the study The objectives of the proposed study are to study the association between the presence of osteoporosis and periodontal disease. We tried to identify the possible connections between particular dietary patterns and therefore the etiopathogenesis of periodontal disease and secondarily of osteoporosis. Materials and methods 110 subjects were recruited in a single-center observational cross-sectional study carried through the collaboration between the University of Florence and the private institute of dentistry Excellence Dental Network based in Florence, suffering of periodontitis, 71 osteoporotic /osteopenic and 39 non-osteoporotic /osteopenic. Anamnestic data and information on eating habits were collected. Results The population showed eating habits that do not meet the intake levels recommended by the L.A.R.N.. Regarding the relationship between nutrient intake and plaque index, it appears that in the population, the higher the intake of vitamin C through food, the lower the plaque index value is. This result could reinforce the scientific evidence that there is a protective factor in the onset of periodontal disease by the consumption of vitamin C which to date is still the subject of investigation. In addition, the same type of trend would also have been observed for calcium intake, but a larger sample size would be required to make this effect significant. Conclusions The relationship between osteoporosis and periodontitis and the role of nutrition in influencing the evolution of these pathologies still seems to be deeply explored. However, the results obtained seem to consolidate the idea that there is a relationship between these two diseases and that eating habits play an important role in their prevention.